Novel bio- based adhesive from cross-linked rice starch-natural rubber latex (nrl) for wood based panels bonding - Gupta, Arun; Soubam, Triveni (2021)
Synthetic adhesive plays an important role in determining the strength of the composite wood panels in the industry. International Agency for Cancer Research (IARC) has declared synthetic adhesive as a threat to human health and environment for emitting carcinogenic gas formaldehyde. The breakthroughs have encouraged researcher to look for a sustainable solution to formaldehyde threat that are derived from natural resources. Bio-adhesive from rice starch and natural rubber latex can open a novel awareness into the design of environment friendly and formaldehyde free composite wood.